Effective thermal conductivity of porous biomaterials: Numerical investigation. (November 2020) - Chikhi, M.
Abstract: The present research paper aims to predict the effective thermal properties; effective thermal conductivity (ETC) and effective thermal diffusivity (ETD) of porous biocomposites materials (PBCs) used as thermal insulator in construction building. The composite matrix consists on porous material namely gypsum reinforced with Date Palm Fibers (DPF). The experimental results of the Effective thermal conductivity (ETC) are obtained using the Ct-meter apparatus. The numerical study is conducted using the finite element Comsol MultiPhysics software resolving the heat transfer equation in stationary state. To evaluate the pores effect on ETC of PBCs, several parameters related on the pores such as its shape, position and weight fraction are considering in the numerical model. The numerical results are fitted with theoretical models and experimental values. The results of this study indicate that the porosity content has an important effect on the ETC of biocompoites whose decreases increasing the pores quantity. It is noted that the numerical models developed in this study are in agree with experimental values for fibers weight content up to 5%. Others parameters are not taken into account such as the pores orientation, contact resistance within the composites may be introduced in the model to minimize the error with the experimental results. The variation effect of pores shapes and positions conserving the same volume on biocomposites ETC are negligible. Highlights: Predict the effective thermal properties of porous biocomposites materials. The numerical study is done using Comsol software resolving the heat transfer equation. The porosity has an important effect on the Effective thermal conductivity biocompoites. The pore shapes and positions effect on ETC is also investigated.